2017
DOI: 10.1016/j.jpedsurg.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Currarino syndrome: does the presence of a genetic anomaly correlate with a more severe phenotype? A multicentre study

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In addition, sporadic cases of CS with a partial duplication of the long arm of the chromosome 3 but no MNX1 mutation have been reported in the literature [ 19 ]. Despite the extreme phenotipic variability observed in patients carrying the same mutation, as well as the incomplete penetrance in familiar cases, recent studies have tried to demonstrate an association between mutation type and severity of the phenotype [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sporadic cases of CS with a partial duplication of the long arm of the chromosome 3 but no MNX1 mutation have been reported in the literature [ 19 ]. Despite the extreme phenotipic variability observed in patients carrying the same mutation, as well as the incomplete penetrance in familiar cases, recent studies have tried to demonstrate an association between mutation type and severity of the phenotype [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of Merello E. et al [ 20 ], that reported a series of CS patients carrying only intragenic mutations, has failed to establish a clear genotype-phenotype correlation. On the other hand, a more recent multicentre Italian study has reported that the presence of a MNX1 anomaly, such as an intragenic mutation or a deletion, was associated to a more severe CS phenotype compared to cases in which no mutation was identified [ 21 ]. Moreover, according to Cuturilo G. et al [ 4 ], intragenic mutations of MNX1 are observed more frequently in patients with the classic Currarino triad and regular growth, normal intellect and facial appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other malformations, most often urologic, can also be associated to the classic Currarino triad. 2 Autosomal-dominant loss-of-function mutations in the MNX1 gene, mapped at 7q36, cause nearly all familial and some (30%) sporadic cases of Currarino syndrome 1 Less frequently, a more complex phenotype (including intellectual disability, growth retardation, and facial dysmorphism) can be caused by microdeletions of 7q containing MNX1.…”
Section: Answer To: Image 2 (Page 1317): Currarino Syndromementioning
confidence: 99%
“…23 Other important European multicenter studies have been coordinated by Italian centers, for example on minimal access adrenal surgery for adrenal pathologies, 24 laparoscopic treatment of pancreatic tumors, 25 the surgical correction technique of congenital Morgagni diaphragmatic hernia 26 ; finally, some important topics have been analyzed by multicenter studies on a national basis, such as bariatric procedures, 27 management of pediatric ovarian torsion and its recurrence, 28 phenotype-genotype correlation in Currarino syndrome. 29 In 2017, the first International Network of Pediatric Airway Teams (INPAT) was created, thanks to the initiative of the Otolaryngology and Pediatric Surgery groups of G. Gaslini Children's Hospital of Genoa. The first INPAT meeting was held in Genoa last March and was a great success, gathering specialists from all over the world.…”
Section: Italian Promoters Of Teamworkmentioning
confidence: 99%